2022
DOI: 10.26650/ase202221031790
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of Can-filling Medium on the DNA Quality of Canned Tuna Sold in Supermarkets

Abstract: Canned tuna is one of the most commonly consumed food products globally. Due to its high profitability and the increasing demand for it, fraudulent canned tuna products have become a serious problem. The traceability of fish species in packaged material and, in the case of highly processed forms, in canned products, has become impossible; therefore, canned tuna is on the list of the top ten food items affected by fraud. These fraudulent actions cause not only unfair trade in the commercial market and fishing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Therefore, treatment with dill extracts has a potential to improve the storage quality of foods such as aquaculture. Similarly, Tümerkan et al (2022) reported that the use of dill leaves in tuna paste preserves the sensory quality of the tuna paste and prolongs its shelf life. In another study, it was reported that fillets treated with dill extracts boiled in a microwave oven had higher sensory scores compared to the control group (Kannaiyan et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, treatment with dill extracts has a potential to improve the storage quality of foods such as aquaculture. Similarly, Tümerkan et al (2022) reported that the use of dill leaves in tuna paste preserves the sensory quality of the tuna paste and prolongs its shelf life. In another study, it was reported that fillets treated with dill extracts boiled in a microwave oven had higher sensory scores compared to the control group (Kannaiyan et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…Kannaiyan et al (2015) showed that due to the antioxidant and antibacterial properties of dill extract boiled in a microwave oven, the shelf life of mackerel fillets stored in the refrigerator was extended by 3 days. Tümerkan et al (2022) revealed that the use of dill leaves extended the shelf life of tuna paste in terms of sensory quality. Even though several researchers have studied dill extracts and essential oils as a natural and edible coating material for seafood products to enhance quality and extend shelf life, to the best of our knowledge, there are no available reports of the effect of dill extract on the shelf life and quality criteria of fish croquettes.…”
Section: Introductionmentioning
confidence: 99%
“…This also to the traceability of food goods, which is crucial for ensuring public health and promoting fair trade. Fraud detection analyses' effectiveness depends on the quality, yield, and degradation level [59], with DNA degradation being a signi cant issue that can lead to interruptions in species identi cation and food traceability. HRNČÍROVÁ et al…”
Section: Economic Evaluation and The Assignability Across The Four Pr...mentioning
confidence: 99%